Polyanionic positive electrode material as well as preparation method and application thereof

The NFPP positive electrode material prepared by stepping sand grinding and freeze-drying solves the problem of poor electrochemical performance of existing NFPP positive electrode materials, and achieves the effects of high reversible capacity, excellent rate performance and good capacity retention.

CN119695087APending Publication Date: 2025-03-25SHANGHAI ELECTRICGROUP CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510103759.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing NFPP positive electrode materials have problems with low electron and ionic conductivity, which leads to a decrease in electrochemical performance during charge and discharge, and it is easy to produce electrochemically inert NaFePO4 during the preparation process.

Method used

By grading the raw materials, they are fully nano- and gelled, and then freeze-drying, and retaining specific morphological characteristics during the calcination process, a quasi-single crystalline sodium ion battery cathode material with a surface coated with carbon layer was prepared.

Benefits of technology

The reversible capacity, rate performance and capacity retention of the material are improved, electron transfer is enhanced, and the strain accumulation of particles during charging and discharging is reduced, thereby improving the structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254881420000091
    Figure BDA0005254881420000091
Patent Text Reader

Abstract

The invention discloses a polyanionic positive electrode material as well as a preparation method and application thereof. The preparation method of the polyanionic positive electrode material comprises the following steps: sequentially sanding, freeze-drying and calcining a mixture of a sodium source, a phosphorus source, an iron source and a carbon source to prepare the polyanionic positive electrode material, wherein two-stage sanding is adopted for sanding; mixed grinding balls are adopted for first sanding, and the mixed grinding balls comprise grinding balls A with the diameter being 1000-2000 microns and grinding balls B with the diameter being 200-1000 microns; the mass ratio of the grinding ball A to the grinding ball B is 1: (1-4); grinding balls C with the particle size of 50-200 microns are adopted in the second sanding; the calcining temperature is 520 to 580 DEG C; the polyanionic positive electrode material prepared by the invention has excellent reversible capacity, rate capability and capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyanion positive electrode material and a preparation method and application thereof. Background Art

[0002] As a key component of sodium-ion batteries, cathode materials have always attracted the attention of researchers. Various types of cathode materials have been reported, including tunnel / layered transition metal oxides, polyanion compounds, and Prussian blue analogs. Compared with Prussian blue analogs and tunnel / layered transition metal oxides, polyanion compounds are considered to be more suitable for large-scale energy storage applications due to their high structural stability, moderate energy density, small volume change, and ultra-long cycle life.

[0003] However, polyanionic materials suffer from poor electronic conductivity, which is mainly attributed to their extensive polyanion networks. These networks have high electronegativity, resulting in an enlarged band gap, which inhibits electron transport. A larger band gap requires additional energy to transfer electrons from the valence band to the conduction band, thus reducing the overall electrochemical performance of the material. Lower conductivity is particularly detrimental to the material's rate performance and capacity retention.

[0004] Among the reported polyanionic compounds, Na4Fe3[PO4]2[P2O7] (NFPP) has become a research hotspot because it combines the advantages of NaFePO4 and Na2FeP2O7. NFPP has a suitable operating voltage and excellent cycle life. Despite this, it still faces the problem of low electronic and ionic conductivity. During the charge and discharge process, the side reaction between the electrode and the electrolyte causes the transition metal ions to gradually dissolve into the electrolyte, which in turn causes the capacity and voltage to decay. In addition, electrochemically inert NaFePO4 is easily produced during the preparation of NFPP, which directly affects its electrochemical performance. Therefore, low conductivity and the presence of inert NaFePO4 are still the main bottlenecks restricting the practical application of NFPP.

[0005] Therefore, achieving large-scale synthesis of high-performance NFPP cathode materials, especially in improving capacity, rate performance and cycle stability, remains a challenge. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defect of poor electrochemical performance of NFPP positive electrode materials in the prior art, and provide a polyanion positive electrode material and a preparation method and application thereof. The present invention performs graded sand grinding on the raw materials to fully nano-size and gelate them, and then freeze-dries them, and fully retains the specific morphological characteristics during the calcination process, thereby preparing a quasi-single-crystal sodium ion battery positive electrode material with a surface-coated carbon layer. The polyanion positive electrode material prepared by the present invention has excellent reversible capacity, rate performance and capacity retention rate.

[0007] The present invention solves the above technical problems through the following technical solutions.

[0008] The present invention provides a method for preparing a polyanionic positive electrode material, which comprises the following steps: sequentially subjecting a mixture of a sodium source, a phosphorus source, an iron source and a carbon source to sand milling, freeze drying and calcining to obtain a polyanionic positive electrode material;

[0009] The sand milling adopts two-stage sand milling; the first sand milling adopts mixed grinding balls, and the mixed grinding balls include grinding balls A with a diameter of 1000-2000 μm and grinding balls B with a diameter of 200-1000 μm; the mass ratio of the grinding balls A to the grinding balls B is 1:(1-4); the second sand milling adopts grinding balls C with a particle size of 50-200 μm; the calcination temperature is 520-580°C.

[0010] In the present invention, the sodium source can be selected from one or more of sodium carbonate, sodium bicarbonate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, sodium oxalate, sodium acetate, sodium citrate, sodium oxide, and sodium peroxide, such as disodium hydrogen phosphate.

[0011] In the present invention, the phosphorus source can be selected from one or more of ferric phosphate, ferrous phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and monosodium trihydrogen pyrophosphate, such as ferric phosphate.

[0012] In the present invention, the iron source can be selected from one or more of ferric nitrate, ferric phosphate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous citrate, ferric oxide, and ferrosoferric oxide, such as ferrous oxalate.

[0013] In the present invention, the carbon source can be selected from one or more of glucose, sucrose, citric acid, stearic acid, oxalic acid, and cellulose, such as glucose.

[0014] In the present invention, preferably, the amounts of the sodium source, the phosphorus source and the iron source are weighed according to the stoichiometric ratio of Na4Fe3[PO4]2[P2O7]; the amount of the carbon source is to maintain the carbon content in the product at 3-5%, where % refers to the mass percentage of carbon in the product.

[0015] More preferably, when the mixture further includes a sulfuric acid source, the sulfuric acid source is weighed in a stoichiometric ratio.

[0016] In the present invention, the mixture may further include a sulfuric acid source.

[0017] Wherein, the sulfuric acid source can be selected from one or more of nickel sulfate, sodium sulfate, ferrous sulfate and ferrous sulfate, preferably nickel sulfate.2- Polyanions can partially replace [PO4] 3- Polyanions further increase the redox potential and improve the electrochemical performance. By doping with nickel, part of the iron element can be replaced, inhibiting the generation of NaFePO4, which is not electrochemically active, during the material preparation process, and further improving the specific capacity of the prepared product.

[0018] In the present invention, in the first sand milling, the mass ratio of the grinding balls A to the grinding balls B is preferably 1:(2-4), such as 1:2, 1:3 or 1:4.

[0019] In the present invention, during the first sand milling, the mass ratio of the mixture to the mixing grinding balls may be 1:(1.5-10), preferably 1:(5-10), such as 1:5, 1:8 or 1:10.

[0020] In the present invention, the sanding time of the first sanding may be 2-5 hours, for example 4 hours.

[0021] In the present invention, during the second sand milling, the mass ratio of the mixture to the grinding balls C may be 1:(5-20), preferably 1:(5-15), such as 1:5, 1:10 or 1:15.

[0022] In the present invention, the sanding time of the second sanding may be 2-10 hours, for example 6 hours.

[0023] In the present invention, during the sand milling process, the phosphorus source, the iron source, and the sulfuric acid source are gelled into a jelly state.

[0024] In the present invention, after the sand milling treatment, the particle size of the obtained solid particles can be 30-500 nm.

[0025] In the present invention, the freeze-drying temperature may be -10 to -25°C, for example -10°C.

[0026] In the present invention, the freeze-drying time may be 2-20 hours, for example 2 hours.

[0027] In the present invention, preferably, the calcination is carried out under an inert atmosphere. The inert atmosphere may be a conventional inert atmosphere in the art, such as nitrogen or argon.

[0028] In the present invention, the calcination temperature may be 530-570°C, such as 540°C, 550°C or 560°C.

[0029] In the present invention, the calcination time may be 6-24 hours, such as 10 hours, 15 hours or 20 hours.

[0030] In the present invention, the calcination may be followed by a pulverization operation.

[0031] The present invention also provides a polyanion positive electrode material, which is prepared by the above preparation method.

[0032] The present invention also provides the use of the polyanion positive electrode material in a sodium ion battery.

[0033] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0034] The reagents and raw materials used in the present invention are commercially available.

[0035] The positive and progressive effects of the present invention are:

[0036] The present invention performs graded sand grinding on raw materials to make them fully nano-sized and gelled, and then freeze-dries them, fully retaining specific morphological features during the calcination process, thereby preparing a sodium ion battery positive electrode material in a quasi-single crystal state with a carbon layer coated on the surface.

[0037] The polyanion positive electrode material prepared by the present invention can reduce the strain accumulation of particles during the charge and discharge process, thereby improving the structural stability of the material during a long cycle. The present invention also increases the electrode-electrolyte interface area, shortens the ion diffusion distance, thereby enhancing electron transfer, and the product has excellent reversible capacity, rate performance and capacity retention rate. DETAILED DESCRIPTION

[0038] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0039] Example 1

[0040] S1, 89g Na2HPO4·2H2O, 75.5g FePO4, 40g FeC2O4·2H2O and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water, and then transferred to a sand grinder for sand grinding to fully gel the raw material. The sand grinding process adopts a graded sand grinding system:

[0041] (1) Preliminary sand grinding: Preliminary sand grinding was performed using mixed grinding balls with diameters of 1000 μm and 500 μm, with the mass ratio of 1000 μm grinding balls to 500 μm grinding balls being 1:4. The above raw materials were mixed with the mixed grinding balls at a mass ratio of 1:5, and after sand grinding for 4 h, the raw materials were separated from the mixed grinding balls.

[0042] (2) Secondary sand milling: Use grinding balls with a diameter of 100 μm for secondary sand milling. The separated raw materials are mixed with grinding balls at a mass ratio of 1:10. After sand milling for 6 hours, the solid particle size of the obtained slurry is between 30-300 nm. The slurry has no obvious water precipitation and stratification within 1 hour, which means that the raw materials have been fully gelled.

[0043] S2. Pour the gelled raw materials into an ice cube mold, the groove of the mold is a cube with a side length of 1 cm. Place the mold in a freezer to freeze the raw materials into ice cubes. Remove the ice cubes from the mold, transfer them to a freeze dryer, and dry them at -10°C for 2 hours.

[0044] S3. The freeze-dried precursor was transferred to a tube furnace, treated at 550° C. for 10 h under a N2 atmosphere, and then cooled to room temperature.

[0045] S4. The calcined product is transferred to a horizontal drum ball mill for pulverization. The powder sample is sieved through 200 mesh, collected, sealed and stored in a desiccator for later use.

[0046] The product is Na4Fe3[PO4]2[P2O7] in stoichiometric ratio.

[0047] Embodiment 2-4

[0048] S1, 89g Na2HPO4·2H2O, 72.48g FePO4, 40g FeC2O4·2H2O, 7.75g NiSO4 and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water. Then it was transferred to a sand grinder for graded sand grinding to make the raw material fully gelled. The graded sand grinding system was the same as in Example 1.

[0049] S2. Pour the gelled raw materials into an ice cube mold, the groove of the mold is a cube with a side length of 1 cm. Place the mold in a freezer to freeze the raw materials into ice cubes. Remove the ice cubes from the mold, transfer them to a freeze dryer, and dry them at -10°C for 2 hours.

[0050] S3. The freeze-dried precursor was transferred to a tubular furnace, and calcined at 550°C for 10 h (Example 2), 550°C for 15 h (Example 3), and 550°C for 20 h (Example 4) under a N2 atmosphere, and then cooled to room temperature.

[0051] S4. The calcined product is transferred to a horizontal drum ball mill for pulverization. The powder sample is sieved through 200 mesh, collected, sealed and stored in a desiccator for later use.

[0052] The product is Na4Fe in stoichiometric ratio. 2.8 Ni 0.2[PO4] 1.8 [SO4] 0.2 [P2O7].

[0053] Example 5

[0054] 89g Na2HPO4·2H2O, 74g FePO4, 40g FeC2O4·2H2O, 3.88g NiSO4 and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water. Then it was transferred to a sand grinder for sand grinding to fully gel the raw material. The graded sand grinding system was the same as in Example 1, and the remaining subsequent steps were the same as in Example 1.

[0055] The product is Na4Fe in stoichiometric ratio. 2.9 Ni 0.1 [PO4] 1.9 [SO4] 0.1 [P2O7].

[0056] Example 6

[0057] 89g Na2HPO4·2H2O, 71g FePO4, 40g FeC2O4·2H2O, 11.62g NiSO4 and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water. Then it was transferred to a sand grinder for sand grinding to fully gel the raw material. The graded sand grinding system was the same as in Example 1, and the remaining subsequent steps were the same as in Example 1.

[0058] The product is Na4Fe in stoichiometric ratio. 2.7 Ni 0.3 [PO4] 1.7 [SO4] 0.3 [P2O7].

[0059] Embodiment 7, 8

[0060] 89g Na2HPO4·2H2O, 75.5g FePO4, 40g FeC2O4·2H2O and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water, and then transferred to a sand grinder for sand grinding to fully gel the raw material. The sand grinding process adopts a graded sand grinding system:

[0061] (1) Preliminary sand grinding: Preliminary sand grinding was performed using mixed grinding balls with diameters of 1000 μm and 500 μm, with the mass ratio of 1000 μm grinding balls to 500 μm grinding balls being 1:4. The above raw materials were mixed with the mixed grinding balls at a mass ratio of 1:5, and after sand grinding for 4 h, the raw materials were separated from the mixed grinding balls.

[0062] (2) Secondary sand milling: The secondary sand milling was performed using grinding balls with a diameter of 100 μm. The separated raw materials were mixed with the grinding balls at a mass ratio of 1:5 (Example 7) or 1:15 (Example 8), and sand milled for 6 h.

[0063] The remaining steps are the same as those in Example 1.

[0064] The product is Na4Fe3[PO4]2[P2O7] in stoichiometric ratio.

[0065] Comparative Example 1

[0066] S1, 89g Na2HPO4·2H2O, 75.5g FePO4, 40g FeC2O4·2H2O and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water. Then it was transferred to a sand grinder for sand grinding to make the raw material fully gelled. The graded sand grinding system was the same as in Example 1.

[0067] S2, removing moisture from the gelled raw material by spray drying.

[0068] S3. The precursor obtained by spray drying is transferred to a tube furnace, treated at 550° C. for 10 h under a N2 atmosphere, and then cooled to room temperature.

[0069] S4. The calcined product is transferred to a horizontal drum ball mill for pulverization. The powder sample is sieved through 200 mesh, collected, sealed and stored in a desiccator for later use.

[0070] The product is Na4Fe3[PO4]2[P2O7] in stoichiometric ratio.

[0071] Comparative Example 2

[0072] S1, 89g Na2HPO4·2H2O, 72.48g FePO4, 40g FeC2O4·2H2O, 7.75g NiSO4 and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water. Then it was transferred to a sand grinder for graded sand grinding to make the raw material fully gelled. The graded sand grinding system was the same as in Example 1.

[0073] S2, spray drying the gelled raw material to remove moisture.

[0074] S3. The precursor obtained by spray drying is transferred to a tube furnace, treated at 550° C. for 10 h under a N2 atmosphere, and then cooled to room temperature.

[0075] S4, the calcined product is transferred to a horizontal drum ball mill for pulverization. The powder sample is sieved through 200 mesh, collected and sealed and stored in a desiccator for later use. The product is Na4Fe 2.8 Ni 0.2 [PO4] 1.8 [SO4] 0.2 [P2O7].

[0076] Comparative Example 3

[0077] S1, 89g Na2HPO4·2H2O, 75.5g FePO4, 40g FeC2O4·2H2O and 18g C6H 12 O6 was dissolved in 500 mL of deionized water by stirring. Then it was transferred to a sand grinder for conventional sand grinding: the raw material and grinding balls were mixed in a mass ratio of 1:10, the grinding balls had a diameter of 100 μm, and the sand grinding lasted for 10 h.

[0078] S2, spray drying the gelled raw material to remove moisture.

[0079] S3. The precursor obtained by spray drying is transferred to a tube furnace, treated at 550° C. for 10 h under a N2 atmosphere, and then cooled to room temperature.

[0080] S4, the calcined product is transferred to a horizontal drum ball mill for pulverization, and the powder sample is sieved through 200 mesh, collected and sealed and stored in a desiccator for later use. The product has a stoichiometric ratio of Na4Fe3[PO4]2[P2O7].

[0081] Comparative Examples 4 and 5

[0082] S1, 89g Na2HPO4·2H2O, 72.48g FePO4, 40g FeC2O4·2H2O, 7.75g NiSO4 and 18g C6H 12 O6 was stirred and dissolved in 500 mL of deionized water. Then it was transferred to a sand grinder for graded sand grinding to make the raw material fully gelled. The graded sand grinding system was the same as in Example 1.

[0083] S2. Pour the gelled raw materials into an ice cube mold, the groove of the mold is a cube with a side length of 1 cm. Place the mold in a freezer to freeze the raw materials into ice cubes. Remove the ice cubes from the mold, transfer them to a freeze dryer, and dry them at -10°C for 2 hours.

[0084] S3. The freeze-dried precursor was transferred to a tubular furnace, and calcined at 500° C. for 10 h (Comparative Example 4) and 600° C. for 10 h (Comparative Example 5) in a N2 atmosphere, and then cooled to room temperature.

[0085] S4. The calcined product is transferred to a horizontal drum ball mill for pulverization. The powder sample is sieved through 200 mesh, collected, sealed and stored in a desiccator for later use.

[0086] The product is Na4Fe in stoichiometric ratio. 2.8 Ni 0.2 [PO4] 1.8 [SO4] 0.2 [P2O7].

[0087] Effect Example 1

[0088] The above-prepared materials were used as active materials to prepare electrodes, and button batteries were assembled for electrochemical performance testing. Active material (AM): binder (PVDF): conductive agent were weighed in a mass ratio of 85:5:10, mixed evenly, and NMP was added to form a uniform electrode slurry, which was then coated on aluminum foil by blade coating. The active material loading was about 3 mg / cm 2 The aluminum foil was then dried in an oven at 80°C for 2 hours, and then transferred to a vacuum drying oven and dried at 105°C for 12 hours before use. Finally, the prepared electrode was compacted with a rolling press, cut into electrode discs with a diameter of 10 mm, weighed, and transferred to a glove box for use as working electrode discs.

[0089] CR 2032 button cells were assembled in the order of positive electrode sheet, separator, and negative electrode sheet. The positive electrode sheet was the working electrode prepared in the present invention, the separator was a commercially available cellgard battery separator, and the Whatman glass Fiber paper is used as absorbent paper, and commercially available After NaPF6 (EC:PC = 1:1) electrolyte, a metal sodium sheet was superimposed as After the negative electrode is formed, the battery is sealed in the glove box, and then the battery is taken out and connected to the battery testing system (Newwell) to test the electrochemical performance of the electrode in the range of 2-4V.

[0090] The test structure is shown in the following table:

[0091]

[0092] It can be seen from the above table that the polyanion positive electrode materials prepared in Examples 1-8 can maintain good reversible capacity and cycle retention rate on the basis of improving rate performance.

[0093] Comparative Example 1 adopts spray drying, which fails to keep the specific morphological characteristics of the precursor, and its rate performance is significantly reduced. Comparative Example 2 adds NiSO4 on the basis of Comparative Example 1, and the reversible capacity of the product obtained is improved, but the rate performance is still poor. Comparative Example 3 adopts conventional sand milling, and the reversible capacity of the product obtained is significantly reduced. The calcination temperature of Comparative Example 4 is too low, and the calcination temperature of Comparative Example 5 is too high, and the reversible capacity and rate performance of the obtained product are both poor.

Claims

1. A method for preparing a polyanionic positive electrode material, characterized in that: It includes the following steps: The mixture of sodium source, phosphorus source, iron source and carbon source is sequentially subjected to sand milling, freeze drying and calcination to obtain a polyanion positive electrode material; The sand milling adopts two-stage sand milling; the first sand milling adopts mixed grinding balls, and the mixed grinding balls include grinding balls A with a diameter of 1000-2000 μm and grinding balls B with a diameter of 200-1000 μm; the mass ratio of the grinding balls A to the grinding balls B is 1:(1-4); The second sand milling uses grinding balls C with a particle size of 50-200 μm; the calcination temperature is 520-580° C.

2. The method for preparing the polyanionic cathode material according to claim 1, characterized in that: In the first sand milling, the mass ratio of the grinding balls A to the grinding balls B is 1:(2-4), for example, 1:2, 1:3 or 1:4; and / or, during the first sand milling, the mass ratio of the mixture to the mixing grinding balls is 1:(1.5-10), preferably 1:(5-10), such as 1:5, 1:8 or 1:10; And / or, during the second sand grinding, the mass ratio of the mixture to the grinding balls C is 1:(5-20), preferably 1:(5-15), such as 1:5, 1:10 or 1:

15.

3. The method for preparing the polyanionic cathode material according to claim 1, characterized in that: The sanding time of the first sanding is 2-5h; And / or, the sanding time of the second sanding is 2-10h; And / or, after the sand milling treatment, the solid particles obtained have a particle size of 30-500 nm.

4. The method for preparing the polyanionic cathode material according to claim 1, characterized in that: The sodium source is selected from one or more of sodium carbonate, sodium bicarbonate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, sodium oxalate, sodium acetate, sodium citrate, sodium oxide, and sodium peroxide, such as disodium hydrogen phosphate; and / or, the phosphorus source is selected from one or more of ferric phosphate, ferrous phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and monosodium trihydrogen pyrophosphate, such as ferric phosphate; And / or, the iron source is selected from one or more of ferric nitrate, ferric phosphate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous citrate, ferric oxide, ferrosoferric oxide, such as ferrous oxalate; and / or, the carbon source is selected from one or more of glucose, sucrose, citric acid, stearic acid, oxalic acid, and cellulose, such as glucose; And / or, the mixture may further include a sulfuric acid source.

5. The method for preparing the polyanionic cathode material according to claim 4, characterized in that: The sulfuric acid source is selected from one or more of nickel sulfate, sodium sulfate, ferric sulfate and ferrous sulfate, preferably nickel sulfate.

6. The method for preparing the polyanionic cathode material according to claim 1, characterized in that: The sodium source, the phosphorus source and the iron source are weighed in a stoichiometric ratio of Na4Fe3[PO4]2[P2O7]; the carbon source is used in an amount to keep the carbon content in the product at 3-5%, where % refers to the mass percentage of carbon in the product; Preferably, when the mixture further includes a sulfuric acid source, the sulfuric acid source is weighed in a stoichiometric ratio.

7. The method for preparing the polyanionic cathode material according to claim 1, characterized in that: The freeze-drying temperature is -10 to -25°C, for example -10°C; And / or, the freeze-drying time is 2-20 hours, such as 2 hours.

8. The method for preparing the polyanionic cathode material according to claim 1, characterized in that: The calcination temperature is 530-570°C, for example 540°C, 550°C or 560°C; And / or, the calcination time is 6-24h, such as 10h, 15h or 20h; and / or, the calcination is carried out under an inert atmosphere; And / or, the calcination may further include a pulverization operation.

9. A polyanionic cathode material, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the polyanionic cathode material according to claim 9 in a sodium ion battery.